Early postoperative outcomes in patients with resectable extrahepatic biliary tumours: A single center cross sectional study - Khursheed, Asfia Arham; Khan, Muhammad Rizwan; Saeed, Javeria (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate early postoperative outcomes in patients having undergone surgery for extrahepatic biliary tumours. Method: The retrospective chart review was conducted in January 2023 at the Aga Khan University Hospital, Karachi, and comprised data of patients who underwent surgical resection of extrahepatic biliary tumours, including hilar cholangiocarcinoma, gallbladder cancer, distal common bile duct tumours and undifferentiated ampullary tumours, between January 2011 and June 2022. Outcomes were assessed in terms of morbidity and 90-day mortality, and the risk factors were determined. Data was analysed using SPSS 25. Results: Of the 81 patients, 47(58%) were males and 34(42%) were females. The overall mean age of the sample was 57.8+-11.4 years. The most common clinical presentation was jaundice 47(58%), while the most frequent site of lesion was ampullary region 50(62%), followed by the gallbladder 22(27%), and the hilar region 9(11%). Postoperative complications were observed in 42(52%) patients, including surgical complications in 28(34.5%). Anastomosis leak was observed in 3(3.7%) patients, and 1(1.23%) required re-exploration. Mortality rate at 90-days was 5(6.2%). The presence of more than two co-morbids and blood loss >500ml were significantly associated with adverse postoperative outcomes (p=0.002). Blood loss >500ml was also associated with 30-day mortality (p=0.003). Conclusion: The overall postoperative outcomes of surgically resected extrahepatic biliary tumours were satisfactory. Key Words: Hepatobiliary, Cholangiocarcinoma, Extra-hepatic biliary tumours, Undifferentiated ampullary tumours, Gallbladder carcinoma.